2018
DOI: 10.1007/s13246-018-0636-9
|View full text |Cite
|
Sign up to set email alerts
|

Fully convolutional networks (FCNs)-based segmentation method for colorectal tumors on T2-weighted magnetic resonance images

Abstract: Segmentation of colorectal tumors is the basis of preoperative prediction, staging, and therapeutic response evaluation. Due to the blurred boundary between lesions and normal colorectal tissue, it is hard to realize accurate segmentation. Routinely manual or semi-manual segmentation methods are extremely tedious, time-consuming, and highly operator-dependent. In the framework of FCNs, a segmentation method for colorectal tumor was presented. Normalization was applied to reduce the differences among images. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…First, VOIs were manually delineated instead of being semiautomatically/automatically segmented, thus making it difficult to avoid subjective errors and making it unsuitable for large-scale data processing [30,31]. Studies had indicated that semiautomated/automated segmentations can provide the reproducible and accurate estimates of the tumor [31][32][33][34]. However, similar to the previous studies, which used manual segmentation in RC patients, these studies described a semiautomated/automated delineated manner along the tumor's outer edge on each consecutive slice, with no precise definition of the border of the whole lesion.…”
Section: Discussionmentioning
confidence: 99%
“…First, VOIs were manually delineated instead of being semiautomatically/automatically segmented, thus making it difficult to avoid subjective errors and making it unsuitable for large-scale data processing [30,31]. Studies had indicated that semiautomated/automated segmentations can provide the reproducible and accurate estimates of the tumor [31][32][33][34]. However, similar to the previous studies, which used manual segmentation in RC patients, these studies described a semiautomated/automated delineated manner along the tumor's outer edge on each consecutive slice, with no precise definition of the border of the whole lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed in colorectal tumor segmentation using different deep learning modules, and the results of segmentation accuracy are acceptable [9]- [11]. However, there are some concerns that the false positive rate is high, and the segmentation edge is rough.…”
Section: Introductionmentioning
confidence: 99%
“…This made the training of this model very slow and expensive. Jian et al proposed an FCN‐based colorectal tumor segmentation method, which provided good results. In their report, they mentioned the problem of class imbalance, but did not further study its impact on segmentation, and the input size of their network was fixed at 96 × 96 pixels.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not completely automatic, as manual intervention is needed during segmentation in some cases. [8][9][10][11] Trebeschi et al 8 proposed an automatic segmentation method for rectal tumors based on convolutional neural networks (CNNs). They extracted a fixed-size patch around each voxel and obtained the segmentation results of these voxels using a trained CNN instance.…”
mentioning
confidence: 99%